Analisis Kepuasan Pengguna Website PPDB Online Dengan Penerapan Metode Webqual 4.0 dan IPA (Studi SMK Negeri 1 Labuan Bajo) - Indriani, Liliosa; Jatmiko, Andriyan Rizki (J-INTECH (Journal of Information and Technology), 2024)
PPDB online is an integrated innovative service website designed by the Province of NTT in collaboration with TELKOM to facilitate and optimize the selection process in the implementation of PPDB (new student registration), the aim of which is to make it easier for prospective new students and their parents at the registration stage. Of course, many students experience difficulties such as registration confusion when they first use the PPDB website because there are too many features on the website. Based on this problem, the following research was carried out in order to understand the extent of user acceptance of the online PPDB website, an analysis of user satisfaction with the website must be carried out. Therefore, an analysis must be carried out regarding the factors that have an impact on the quality of user satisfaction. The aim of this research is to analyze the quality of the online PPDB website based on user satisfaction using the Webqual 4.0 and Importance Performance Analysis (IPA) methods. Webqual 4.0 is determined as a questionnaire preparation flow and Importance Performance Analysis (IPA) is determined as an analysis tool in the form of Gap Analysis and Cartesian quadrants. This research used accidental sampling with the number of respondents being 1,575 active students at SMK Negeri 1 Labuan Bajo with the total sample in this study being 94 students at SMK Negeri 1 Labuan Bajo class Slovin's formula. Based on the results of the level of conformity on the PPDB Online website, the usability variable is 104.84%, the information variable is 96.05%, and the interaction variable is 103.09%. This shows that the indicators for information quality, the actual quality (performance) perceived by users, are not in accordance with the expected ideal quality (importance). The results of the gap level on the PPDB Online website for the usability, information, interaction and user satisfaction variables are 0.014817, the gap value is positive 0, meaning the quality of the website meets user needs. However, there are still several indicators in the importance performance analysis (IPA) quadrant that do not meet user satisfaction.